Essays on Asset Return and Housing Market - (:unkn) unknown (My University, 2013)
The last two decades have witnessed substantial amount of research on time variation in asset returns. It has been found that macroeconomic variables contain useful information about asset returns. This dissertation consists of three essays that study the link between the macroeconomy and financial markets. A central idea behind the link is that households adjust their consumption spending in anticipation of variations in the return on household assets. The first essay proposes a latent-variables approach to estimate expected returns on total household assets and expected growth rate of excess consumption (consumption in excess of labor income) within a present-value model of consumption. The present-value model of consumption implies that the ratio of consumption- aggregate wealth reflects information about future asset returns and consumption growth. Since expected returns and expected excess consumption growth are unobserved variables, the current literature uses lagged excess consumption-assets ratio or other proxies for estimation. This essay goes beyond the existing literature by using an unobserved component approach to filter these unobserved variables from the observed history of realized returns and realized excess consumption growth. Results suggest that both filtered returns and filtered excess consumption growth rate are significant and better predictors of realized returns and realized excess consumption growth rate than the one obtained by lagged excess consumption-assets ratio. The second essay focuses on estimating expected return on housing by exploiting the information from the movements in consumption, income, and observable assets. To do so, a present-value model of consumption is combined with an unobserved component model. Kalman filter is then applied to extract expected housing returns from the observed history of realized returns and realized excess consumption growth. Results suggest that the filtered housing returns does a significantly better job in predicting realized housing returns than other popular predictors like mortgage rate and price-rent ratio. The third essay uses an unobserved components model with heteroskedastic disturbances to measure the time-varying importance of permanent and transitory components in the U.S. and U.K. house prices. Estimation results suggest that the movement in house prices in the two economies is mainly transitory in nature from its trend path.
Keywords: Asset Returns; Housing Market; Unobserved Component